SOCIOECONOMIC CHARACTERIZATION OF RURAL PRODUCERS AND AGRICULTURAL PRODUCTION SYSTEMS OF THE MUNICIPALITY OF PALMITAL/SP - Bianchi, V. R.; De Oliveira, S. C.; Pinto, L. B. (Revista Brasileira de Engenharia de Biossistemas, 2018)
The objective of this article is to present an analysis of the profile of rural producers, of production and of agricultural production systems in the municipality of Palmital/SP. This is a descriptive research with qualitative approach, in which the data were analyzed by means of tools based on descriptive statistics (tables, graphs, descriptive measures, etc.). As results, is presented a broad socioeconomic description of rural producers, as well as activities and of agricultural products that stand out most in the municipality, besides characterization and quantification of production systems. Although there is greater emphasis on vegetable production with strong influence of three products (sugarcane, corn and soybeans), twenty-six production systems were found (ranging from one to seven products), showing a great diversity of socioeconomic strategies maintenance of rural producers, mainly family members. Thus, expected contribute to the elaboration of strategic lines of rural development, this is, for the definition of public policies, of action programs and of projects (government, producer organizations, NGOs, etc.), starting from the agricultural characteristics described on the said municipality.